The missing construct: Impathy - Neubrand, Stefanie; Gaab, Jens (Frontiers in Psychology, 2022)
This article is about impathy (introversive empathy), the ability to share in and understand one’s own feelings, which is considered a critical psychological approach for the recovery and maintenance of mental health. However, while the ability to empathize with oneself has received considerable attention from the clinical community, this has not been paralleled by the same scientific scrutiny which was subject to the ability to empathize with others. Impathy has not yet been operationally defined and thus has remained relatively unexplored, both conceptually and empirically. This work describes an operational definition of impathy with four dimensions: Internal Attention, Meta-Position, Accepting Attitude, and Understanding. Issues of differentiation from related constructs are discussed and avenues of clinical applicability are explored, suggesting that impathy exists as a distinct human capacity, which can be assessed and which has important clinical implications. The paper closes with reference to our own questionnaire approach to impathy research.